The value based approach to treat diabetes. The case of Puglia Region - Emanuela Maria Frisicale; Pasquale Cacciatore; Umberto Finelli; Carlo Favaretti; Stefania Boccia; Andrea Silenzi (Epidemiology, Biostatistics and Public Health)
No abstract are available